Praktik Perencanaan dan Pelaksanaan Pembelajaran Puisi Modern di Kelas VIII SMP: Studi Kasus Kualitatif - Herman Didipu; Sri Abelia Noho; Moh. Rizaldi; Fendra Amelia Abdullah; Sastia Minasi Asuke (PT Cendekia Education Center, 2026)
The teaching of modern poetry at the junior high school level faces various challenges, ranging from low student engagement to the gap between lesson planning and implementation. This study aims to describe the practices of planning and implementation, as well as the issues that need to be addressed in the teaching of modern poetry in eighth-grade junior high school classes. The study employs a qualitative approach using a single-case study design. The research subject was an Indonesian language teacher at a selected junior high school chosen for their strong pedagogical competence and relevant teaching experience. Data were collected through three phases: pre-observation (planning interviews and documentation), classroom implementation observation by a team of four observers, and post-observation (problem identification interviews). Data analysis followed the interactive model by Miles, Huberman, & Saldaña. The results of the study indicate that the teacher developed adaptive and contextual lesson plans by tailoring the material to students’ abilities and analyzing effective weeks for the preparation of annual, semester, and daily programs. The syllabus was developed flexibly, referencing government guidelines but adapted to the school’s conditions and students’ characteristics. In practice, teachers interpret the elements of poetry (diction and imagery) through contextual texts such as newspapers. The learning process is reflective and responsive, incorporating peer-tutoring strategies, feedback directed toward other students, and ongoing reflection for revising teaching modules. Identified issues include digital media management, a decline in student focus during critical hours, low emotional engagement among students, and a gap between the theory learned in teacher training institutions and practice in the field. This study implies the need to strengthen the field practice component in the curriculum for prospective teachers and to foster a culture of continuous reflection among teachers.